Versatility of the Keystone Design Perforator Island Flaps in Resurfacing Soft Tissue Defects - Sahu, Ranjit Kumar; Mahadik, Kaushik; Giri, Sanjay Kumar; Suba, Santanu; Mallik, Mainak; Panda, Ritesh; Kanungo, Aparna; Minz, Reena; Rout, Sunil Kumar (Indian Journal of Plastic Surgery, 2024)
Background The keystone design perforator island flap (KDPIF) is unique among local flaps because of its high potential for adaptation. We describe our experience with the use of the keystone flap for the reconstruction of a variety of defects in different regions of the body concerning its versatility, surgical outcomes, complications, postoperative pain, operative time, and esthetic outcomes.Methods A prospective observational study was conducted at our institute from June 2021 to June 2023 where the use of KDPIFs in resurfacing soft tissue defects of different etiopathogenesis was evaluated and the data were analyzed.Results Forty-four patients were included in the study with soft tissue defects of various etiologies and at different locations. The largest flap raised was 18 × 10 cm and the smallest was 4 × 2 cm. The average intraoperative time for completion of the procedure was 74.86 minutes (range: 45–120 minutes). The success rate of flap survivability was 95.45% with two patients having total flap loss necessitating another reconstructive option. Partial flap dehiscence which healed secondarily was observed in two patients. Postoperative pain showed a significant fall of 83.7% from baseline and 82.9% of cases were extremely satisfied with the esthetic outcome.Conclusion The keystone flap is a valuable reconstructive tool in the armamentarium of a plastic surgeon. It is technically reproducible, suitable to be done in resource-limited settings, and provides contiguous tissue with good vascularity and fewer complications.
Keywords: keystone flap; island flap; local flap'